Saúde do trabalhador docente no ensino superior privado sob a perspectiva da Psicologia Social - Andrade, Lidiane dos Anjos Santos (2018)
Understanding the University as a space of psychosocial transformative and emancipatory action, we seek to analyze the precariousness of teachers' work, understanding their social relevance in the historical course, and in a relationship with the Government, the society, the capitalist ideology and the daily work. This study proposes, based on a general analysis of the relations of Capitalism with the themes of research – as Work and Education – to establish ways of overcoming alienation for an effective social transformation, from the speech of the teachers that creates daily the environment to education. For that, a quantitative-qualitative research was carried out from a questionnaire available online to the target public: private higher education teachers in Brazil. The results point to a confirmation of education as a commodity and the teacher as subservient to this culture established by a new model of education in the country, analyzed in a socio-historical context